1962
DOI: 10.1083/jcb.14.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy of the Human Synovial Membrane

Abstract: The structure of the lining cclls at the surface of the synovial membrane facing the joint cavity has been studied by elcctron microscopy. The long cytoplasmic processes of these cells appear to be oriented toward the surface of the membrane, where they overlap and intertwine. The matrix of the lining cells contains dense material but no fibers with thc periodicity of collagen. The lining cells are divided into two cell types or states of activity on the basis of their cytoplasmic contcnts. Type A is more nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
198
2
6

Year Published

1969
1969
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 501 publications
(216 citation statements)
references
References 15 publications
10
198
2
6
Order By: Relevance
“…In the present study, EM revealed 3 different patterns of DR staining in the lining area of RA synovium. Strongly DR+ lining cells were identified as the type A, or macrophage-type, cells described by Barland et a1 (28), and largely DR-cells were identified as the type B, or fibroblast-type, cells. Intermediately staining DR+ cells of a type previously described as type I1 (37) or type C cells (38,39) were also observed.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In the present study, EM revealed 3 different patterns of DR staining in the lining area of RA synovium. Strongly DR+ lining cells were identified as the type A, or macrophage-type, cells described by Barland et a1 (28), and largely DR-cells were identified as the type B, or fibroblast-type, cells. Intermediately staining DR+ cells of a type previously described as type I1 (37) or type C cells (38,39) were also observed.…”
Section: Discussionmentioning
confidence: 79%
“…The strongly DR+ cells had numerous irregular cytoplasmic processes, many lysosomes, vacuoles, and filopodia, indicating that these cells were of the macrophage lineage and, therefore, were type A lining cells (28,29). Type B lining cells, which had a round shape, eccentric nucleus, well-developed rough endoplasmic reticulum, and Golgi apparatus, were either negatively stained or showed very weak DR staining ( Figures 3A and B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lining layer of the synovial membrane contains two kinds of lining cells: macrophage-like type A and fibroblastic type B cells (Barland et al, 1962;Graabaek, 1984). We were unable to observe all organellae in the ER␣-positive cells due to the use of GMA resin, which is disadvantageous for detailed observations.…”
Section: Discussionmentioning
confidence: 83%
“…Many ultrastructural investigations have pointed out that the synovial membrane consists of two kinds of synovial lining cells: macrophage-like type A and fibroblastic type B cells (Barland et al, 1962;Graabaek, 1984). In rodents, type A cells are characterized by numerous vesicles, vacuoles, and lysosomes, while type B cells possess a well-developed rough endoplasmic reticulum and a number of dense secretory granules.…”
mentioning
confidence: 99%